Exploration on the Governance of Wells with Deficient Liquid Supply in B Block. Issue 4 (February 2019) - Sun, Mingyan
Abstract: By directing at wells with deficient liquid supply in B Block of A development area, this paper made a comprehensive analysis on the causes for wells with deficient liquid supply by utilizing static, dynamic and fine geological research achievements from the aspects of engineering and geology. It summarized two categories and 8 subclasses of factors resulting in deficient liquid supply of mechanical oil production wells, and proposed corresponding governance countermeasures. Comprehensive governance was conducted for 42 wells with deficient liquid supply, which can provide references for the governance of other wells.